A meta-analysis on correlation between interleukin-6 -174G/C polymorphism and end-stage renal disease. (1st January 2017) - Feng, Ye; Tang, Yan; Zhou, Hongwei; Xie, Kaiqing
Abstract: Background: The level of interleukin-6 (IL-6) and its gene polymorphism are associated with the end-stage renal disease (ESRD) and the related complications. This study aimed to investigate the correction between IL-6 -174G/C polymorphism and ESRD by meta-analysis. Methods: Using the databases including PubMed, Embase, Cochrane library, CNKI, and CBM, the data of case-control studies on correlation between IL-6 -174G/C polymorphism and ESRD from database establishment to January 2016 were collected. According to inclusion and exclusion criteria, the quality of literatures was evaluated. The relevant research data were extracted, followed by meta-analysis using Revman 5.3 software (London, UK). The combined odds ratio (OR) and 95% confidence interval (95%CI) of each genetic model were calculated, and the publication bias data was assessed using the Stata 12.0 software (College Station, TX). Results: A total of five literatures were included, with 1199 cases in case group and 1089 cases in control group. Meta-analysis showed that, there was no significant correlation between each genetic model of IL-6 -174G/C polymorphism and ESRD [(C versus G): OR = 1.36, 95%CI (0.69, 2.66), p = .38; (CC + GC versus GG): OR = 1.28, 95%CI (0.58, 2.82), p = .54; (CC versus GG + GC): OR = 1.71, 95%CI (0.82, 3.54), p = .15; (CC versus GG): OR = 1.74, 95%CI (0.76, 3.99), p = .19; (GC versus GG): OR = 1.18, 95%CI (0.55, 2.54), p = .67]. The race subgroup analysis showed that, there was no significant correlation between each genetic model of IL-6 -174G/C polymorphism and ESRD in the Caucasians ( p > .05). Conclusion: IL-6 -174G/C polymorphism has no significant correlation with the susceptibility risk of ESRD, and may not be a risk factor for ESRD.